â€œHOPEâ€ Learning Model to Improve Elementary School Students in Understanding of The Tentative Aspect Nature of Science (NOS) - Sukmana, Rika Widya; Widodo, Ari (PrimaryEdu : Journal of Primary Education, 2023)
The "HOPE" learning model is used to determine differences in understanding the nature of science (NOS) in tentative aspects of elementary school (SD) students before and after learning. The method used is pre-experimental with one group pre-test and post-test design. The respondents of this study consisted of 32 public elementary school students. Questionnaires for understanding the nature of science and interview sheets are the instruments of this study. The data obtained were analyzed by Wilcoxon test using SPSS ver. 23 at Î± (0.05). The results of the study showed that there were differences in understanding the nature of the tentative aspects of science in students before and after learning using the "HOPE" model. It can be concluded that the "HOPE" learning model has an effect on increasing understanding of the nature of science in the tentative aspect.